2008
DOI: 10.1080/00140130701711000
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of posture and muscle activity during tablet computer, desktop computer and paper use by young children

Abstract: Computers are now widely used by children. Tablet computers are becoming widely available and promoted for use by school children. The primary objective of this study was to compare the posture and muscle activity of children using a tablet computer to the posture and muscle activity of children using a desktop computer and paper technology. Eighteen children (mean age 5.6 years) performed a colouring-in task in tablet, desktop and paper conditions. 3-D posture and muscle activity around the neck and shoulder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 27 publications
4
105
0
3
Order By: Relevance
“…Variability of adult posture and muscle activity was also compared to that of children aged 10-12 years and 5-6 years (Maslen and Straker 2009). An evaluation of tablet computers has also been conducted (Straker et al 2008b).…”
Section: Progress Towards Evidence-based Child Specific Guidelinesmentioning
confidence: 99%
“…Variability of adult posture and muscle activity was also compared to that of children aged 10-12 years and 5-6 years (Maslen and Straker 2009). An evaluation of tablet computers has also been conducted (Straker et al 2008b).…”
Section: Progress Towards Evidence-based Child Specific Guidelinesmentioning
confidence: 99%
“…And also MSD is related to manual tasks and is a source of significant pain, disability and substantial burden on modern societies. Statistics showed that more than 30% of all occupational injuries are musculoskeletal injuries associated with manual tasks [3].WMSD have also heavy economic costs to the companies and to health care systems. The costs are due to loss of productivity, training of new workers and compensation costs [4].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Information and communication technology (ICT) plays an ever more important role in the current workplace and as a result computer use has greatly increased in recent decades (IJmker et al 2007, Straker et al 2008, Yoshioka et al 2008. Unfortunately, arm, shoulder and neck symptoms are common amongst computer workers and are suggested to be work-related (Punnett and Bergqvist 1997, Ekman et al 2000, Palmer et al 2001, Brandt et al 2004, Wahlstrom 2005, Woods 2005, Robertson et al 2009).…”
Section: Introductionmentioning
confidence: 99%